Benthic microalgae assemblages of Asajaya Mangrove area, Kota Samarahan, Sarawak - Mohd Nasaruddin, Harith @ Abdul Nasir (Universiti Malaysia Sarawak (UNIMAS), 2006)
This study aimed to record the benthic microalgae assemblages and distribution in mangrove area of Asajaya. The sampling included the sediment and non-sediment (rocks and roots) samples from four stations that was set. The benthic microalgae were identified until the genus level and the number of individual per mil1ilitre sample were determined. The assemblages was varied between stations and dominated by pennate diatom genera. A total of 22 diatom genera and 5 genera of cyanobacteria were identified. The most common microalgae occurred at every sampling station was diatoms which were Achnanthes, Amphora, Asterionella, Coscinodiscus, cyclotella, Cymbella, Diploneis, Fragilaria, Gomphonema, Gyrosigma, Navicula, Nitzschia, PinnUlaria and Synedra. For cyanobacteria, the genera identified were Anabaena, Chroococcus, Lyngbya, Oscillatoria and Synechococcus. No dinoflagellates were identified in this study.